Linguistic sustainability: A tripartite analysis of eco-translation’s impact on environmental governance, food security, and water sanitation across selected SDGs - Alshaikhi, Turky; Sagir Khan, Aayesha; Alharahsheh, Abdelrauof Meqbel; Ismail, Sayed M. (Research Journal in Advanced Humanities, 2025)
The United Nations Agenda for 2030 encounters a significant challenge as primarily ecological terms are available only in English, French, and Spanish. This creates a language gap that excludes rural and indigenous communities who speak other languages —including those in Arabic-speaking countries—, preventing them from fully understanding, engaging with, and implementing the sustainable development goals. Therefore, the present study not only aims to analyse critically the translations of the ecological terms from English to Arabic but also it employs an Eco-Translation framework to analyse how linguistic mediation directly impacts the efficacy of policies and practices related to environmental sustainability and basic human needs. The study adopts a qualitative case study approach through which it analyses the translations from English into Arabic to terms focused on SDG 6 (Clean Water and Sanitation), SDG 13 (Climate Action), and SDG 15 (Life on Land), as it addresses how the translation/mistranslation of technical, legal and community-based texts affects outcomes in environmental conservation, food security and public health. The findings aim to establish a robust argument for integrating professional translation and localization into the core strategy of international development initiatives.